Exploring Current Practices, Challenges, and Innovations in the Nutrition and Feeding of Neonates, Including the Use of Human Milk, Fortifiers, and Formula: A Clinical Study - Partha K. Chaudhuri; Abha Madhur; Kumar Anshu; Shiromani Kumari; Ashutosh; Jyotsna Singh; Barapatla Sarangam; Pratik Sarkar (Wolters Kluwer Medknow Publications, 2024)
Background: Neonatal nutrition plays a crucial role in the growth and development of infants, particularly in the neonatal intensive care unit (NICU) where specialized care is essential. This study aims to explore current practices, challenges, and innovations in the nutrition and feeding of neonates, focusing on the utilization of human milk, fortifiers, and formula. Materials and Methods: A retrospective clinical study was conducted at a tertiary care NICU over a period of two years. Data were collected from medical records of neonates admitted to the unit. Information regarding feeding practices, types of milk (human milk, fortified human milk, or formula), fortification protocols, and associated clinical outcomes were analyzed. Results: A total of 150 neonates were included in the study. The majority (85%) received some form of human milk during their NICU stay, with 60% exclusively receiving human milk. Among those receiving human milk, 40% required fortification with a human milk fortifier due to inadequate growth parameters. Formula supplementation was necessary in 25% of cases due to maternal lactation insufficiency or medical contraindications to human milk. The mean duration of parenteral nutrition was 10 days, with a median time to full enteral feeds of 14 days. Infants receiving exclusively human milk demonstrated a lower incidence of necrotizing enterocolitis (NEC) compared to those receiving formula (5% vs. 12%, P < 0.05). Conclusion: Human milk remains the preferred source of nutrition for neonates in the NICU setting, associated with lower rates of NEC and improved clinical outcomes. However, fortification with human milk fortifiers or supplementation with formula is often necessary to meet the nutritional requirements of preterm infants. Further research is needed to optimize fortification protocols and improve long-term outcomes in this vulnerable population.